Low-Voltage Ablation in Persistent Atrial Fibrillation - Astrid Paul Nordin; Emmanouil Charitakis; Carina Carnlöf; Finn Åkerström; Ott Saluveer; Henrik Almroth; Lars O. Karlsson; Anders Hassel Jönsson; Csaba Herczku; Jari Tapanainen; Niklas Höglund; Emma Svennberg; et al. (JAMA, 2026)
Importance Pulmonary vein isolation remains the foundational ablation approach for atrial fibrillation (AF), yet outcomes in persistent AF remain suboptimal. Targeting low-voltage zones identified by electroanatomical mapping offers a promising strategy for enhancing ablation success. Objective To determine whether adjunctive individualized low-voltage zone ablation improves arrhythmia outcomes and health-related quality of life beyond pulmonary vein isolation alone in patients with persistent AF and significant low-voltage zones. Design, Setting, and Participants Multicenter randomized clinical trial with 12 months of follow-up conducted at 5 Swedish ablation centers between May 18, 2020, and April 9, 2026. Of 936 adult patients undergoing first-time ablation and voltage mapping for persistent AF, 209 with low-voltage zones of 3.0 cm 2 or greater were randomized. Interventions Following pulmonary vein isolation, patients with significant low-voltage zones were randomized to either receive individualized adjunctive low-voltage zone ablation (n = 102) or receive no further ablation (n = 107). Main Outcomes and Measures The primary outcome was freedom from documented atrial arrhythmia without antiarrhythmic drugs at 12 months after 1 or 2 ablation procedures within 6 months. Secondary outcomes were time to first recurrence after a single procedure without antiarrhythmic drugs, health-related quality of life, and safety. Results Among the 209 randomized patients (median age, 72 years; 109 females [52.2%]), the primary outcome was achieved more frequently in the pulmonary vein isolation plus low-voltage zone ablation group than in the pulmonary vein isolation alone group. Arrhythmia-free survival was achieved in 69 patients (67.6%) vs 40 patients (37.4%), respectively (unadjusted difference, 30.3% [95% CI, 17.4%-43.2%]; odds ratio, 3.5 [95% CI, 2.0-6.2]; P < .001). Time to first recurrence after a single ablation procedure without antiarrhythmic drugs also favored low-voltage zone ablation (hazard ratio, 0.4; 95% CI, 0.3-0.6; P < .001). Improvements in health-related quality of life were greater in the low-voltage zone ablation group, whereas rates of serious adverse events were similar between groups. Conclusions and Relevance Adjunctive low-voltage zone ablation added to pulmonary vein isolation improved rhythm outcomes and health-related quality of life without increasing serious adverse events in patients with persistent AF and significant low-voltage zones. These findings support a low-voltage zone–guided ablation strategy in this population. Trial Registration ClinicalTrials.gov Identifier: NCT04377594